Analysis of phase bias between GNSS signal components caused by nonideal group delay. Issue 2 (9th June 2020) - Liu, Yuqi; Yang, Yi; Chen, Lin; Pan, Hongchen; Ran, Yihang
Abstract: Binary offset carrier (BOC) modulations are widely used in the modernized satellite navigation systems. But we find an interesting phenomenon that the signal composed of different BOC modulations suffers larger phase bias than the case that all the components have the same modulation due to the nonideal group delay of the channel. This issue is more obvious in navigation satellites for the use of a narrowband filter to suppress the out‐of‐band part. The general form of analytic expression that reveals the impact of the nonideal channel on phase bias is presented and validated with simulations. Further, by simplifying the spectrums for the signals like B1 of BeiDou and E1 of Galileo navigation systems, we obtain the concise expression of phase bias and find that the bias is mainly derived from the phase difference between the subcarrier frequencies caused by the odd order terms of group delay.